The presumption of the syntactic sign and its impact on linguistic structures (Applied study on the poetry of Al-Kumait bin Zaid Al-Asadi) - صفية, وحيد; حاج حسين, هلال رياض (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The presumption of the syntactic sign is one of the most prominent grammatical clues, as it has an important impact in defining and directing the meaning, distinguishing the locations of syntax vocabulary, and clarifying the cases of syntax. Most of the Arab grammarians believe that the parsing in the Arabic language has a great impact on the performance of the meaning, removing confusion and ambiguity in most cases, and they also see that the parsing also has a great advantage represented in giving the word freedom of composition in terms of introduction and delay without the word losing its function, And this is a feature that distinguished the Arabic language over others as it is an Arabized language, while the non-Arabized languages ​​adhere to the word in one rank, and thus lose a great deal of flexibility that can be afforded by the presence of parsing. Proceeding from all the progress, this research came to shed light on the importance of this presumption and its role in clarifying the meaning, revealing confusion and removing ambiguity, applying this to the poetry of Al-Kumait bin Zaid Al-Asadi, whose poetry combined the integrity of the composition, the durability of style, and the fulfillment of meaning.